The Influence of Roughness on the Properties of Electroactive Polypyrrole - Sylwia Golba; Julian Kubisztal (Molecules)
This study describes the properties of electroactive polypyrrole and its applications, with a focus on the roughness of the material. This parameter is crucial as it influences the applicability of coated layers, leading to highly adherent coatings or programmed wettability. The first raised aspect covers the electrodeposition procedure, which can help tailor the desired smoothness determined by roughness parameters. Features such as the deposition method, synthetic solution components, potential boundaries, substrate type, and utilized additives are evaluated. In the following section, the application aspects are discussed with a focus on modern, currently developed subjects such as medical applications, including cell-adherent coatings, antibacterial coatings, and drug delivery modules, as well as more technological fields like improved adhesion to the substrate and the improved mechanical properties of the deposited coating.